PENERAPAN METODE PEMBELAJARAN PETA PIKIRAN ( MIND MAPPING ) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV C DI SDN 59 SEBANGAR - Dewi Lestari; Hamizi Hamizi; Erlisnawati Erlisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem in this research was social studies students achievement in fourth graderes (IVC) SDN 59 Sebangar still low with average value 53,23 (with KKM 65 ). The purpose of this research was to improve the students achievement of the fourth graderes (IVC) SDN 59 Sebangar with the implementation of mind mapping method. This research was a classroom action research with two cycles in second semester 2014/2015. Before implementation mind mapping method average 53,23, after implementation of mind mapping method, UH 1 was 66,92 that improve 16,89% from before exam with average 53,23. UH 2 was 79,04 that improve 30,64%. Teacher’s activities with the implementation of mind mapping method at first meeting of first cycle was 57,14% ( enough category ), and second meeting was 78,57% ( good category ) that improve 21,43 point. At second cycle, teacher’s activities was 82,14% ( good category ) that improve 3,57 point from second meeting of first cycle. Second meeting of second cycle was 89,29% ( everygood category ) which improve 7,14 point. Implementation of mind mapping method can improved social studies students achievement of fourth graderes (IVC) SDN 59 Sebangar.Key Words : Mind Mapping Method, Social Studies Student’s Achievement